Extreme Growth Failure is a Common Presentation of Ligase IV Deficiency. Issue 1 (8th November 2013) - Murray, Jennie E.; Bicknell, Louise S.; Yigit, Gökhan; Duker, Angela L.; van, Margriet; Haghayegh, Sara; Wieczorek, Dagmar; Kayserili, Hülya; Albert, Michael H.; Wise, Carol A.; Brandon, January; Kleefstra, Tjitske; et al.
<x xml:space="preserve">Abstract</x> Ligase IV syndrome, a rare disorder of DNA damage repair, is associated with severe immunodeficiency, malignancy predisposition, and microcephaly. Here, we report that mutations in LIG4 also occur in patients presenting with extreme growth failure, extending the phenotypic spectrum of Ligase IV deficiency. A correlation between degree of protein truncation and disease severity is observed, with a recurrent mutation presenting in conjunction with a more severely truncating mutation conferring profound growth impairment with progressive bone marrow failure and immunodeficiency. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>